(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
In the current study, gastro-retentive tablets of Ritonavir was developed to increase its oral bioavailability using hydrophilic polymers HPMC K 4M, K 15M, and K 100M as release retarding agents. Polyox WSR 303 was chosen as resin, sodium bicarbonate was used as effervescent agents. The tablets were prepared by direct compression method and FTIR studies revealed that there is no interaction between the drug and polymers used for the formulation. Among all the formulations F21 containing HPMC K 100M, Crospovidone, Polyox WSR 303 and sodium bicarbonate, as gas generating agent was choosen as optimized formulation based on the evaluation parameters, floating lag time (33 sec) and total floating time (>24 h) and in vitro dissolution studies. From in vitro dissolution studies, the optimized formulation F21 and marketed product was shown 98.67% and 95.09 ± 5.01% of drug release respectively. From in vivo bioavailability studies, after oral administration of floating tablet containing 100 mg Ritonavir, the Cmax, Tmax, and AUC0–∞ of optimized gastroretentive formulation were found to be 30.11 ± 1.16µg/mL, 8.00±1.23 h and 173 ± 26.34µg*h/ml, respectively. Cmax and AUC values of optimized formulation were found to be significantly higher than of marketed product, where longer gastric residence time is an important condition for prolonged or controlled drug release and also for improved bioavailability.